ä½¿ç”¨å¡ç‰‡æ•™å…·æé«˜é“æˆ¿åˆä¸ç¬¬ä¸‰å…«å¹´çº§å¦ç”ŸKecamatan Hulu Sungaiæ±‰è¯ è¯æ±‡è®°å¿†åŠ› - Huda, Munawir; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn order to speak good Chinese, first of all to master a certain number of words. But for some people the biggest problem is memory. It is easy to forget that the reason may be that students feel difficult for Chinese and lose interest. Because it is not interested, it is easy to forget. In order to solve this problem, the author will use the card method to study thispaper.The author studies the 22 students of the eighth year of the National Junior High School Kecamatan Hulu Sungai. Explore whether the use of card teaching aids can improve students' memory. The author of the pre-test and post-test after the test and post-test results for statistical analysis and analysis. The results of card teaching aids can improve student memory, and improve students' understanding of the meaning of words. Keywords: Â vocabulary teaching, card, memory